Comparison between radial versus femoral percutaneous coronary intervention access in Indonesian hospitals, 2017–2018: A prospective observational study of a national registry. (April 2020) - Alkatiri, Amir Aziz; Firman, Doni; Haryono, Nur; Yonas, Emir; Pranata, Raymond; Fahri, Ismir; Artha, I Made Junior Rina; Pratama, Vireza; Widodo, Wishnu Aditya; Taufiq, Nahar; Alkatiri, Abdul Hakim; Ng, Sunanto; et al.
Abstract: Background: Coronary heart disease is a leading cause of death in Indonesia and percutaneous coronary intervention (PCI) is a routinely performed procedure. The aim of this study is to provide real-world insight on the demographics of coronary artery disease and comparison between radial compared to femoral PCI in Indonesia, which performed radial access whenever possible. Methods: This is a prospective cohort study involving 5420 patients with coronary artery disease who underwent PCI at 9 participating centers in the period of January 2017–December 2018. Results: Radial access rate was performed in 4038 (74.5%) patients. Patients receiving femoral access has a higher rate of comorbidities and complex lesions compared to radial access. The incidence of in-hospital mortality, cardiogenic shock, major arrhythmia, and tamponade were higher in femoral group. The incidence of in-hospital mortality was 114 (2.1%). New-onset angina (OR 3.412), chronic renal failure (OR 3.47), RBBB (OR 4.26), LBBB (OR 6.26), left main stenosis PCI (OR 3.58), cardiogenic shock (OR 4.9), and arrhythmia (OR 15.59) were found to be independent predictors of in-hospital mortality. Radial access did not independently affect in-hospital mortality. In propensity-matched cohort, radial access was not associated with lower in-hospital mortality in both bivariable and multivariable model. However, radial access was associated with reduced in-hospital mortality in STEMI subgroup (OR 0.31). Conclusion: Higher rate of adverse events was noted on the femoral access group. However, it might stem from the fact that patients with more comorbidities and complex lesions are more likely to be assigned to femoral access-group. Neither radial or femoral access is superior in terms of in-hospital mortality upon propensity-score matching/multivariable analysis.